Analysis of Olive Oil Market Volatility using the ARCH and GARCH techniques - Gontijo, Tiago Silveira; Rodrigues, Alexandre de Cássio; De Muylder, Cristiana Fernandes; la Falce, Jefferson Lopes; Pereira, Thiago Henrique Martins (International Journal of Energy Economics and Policy, 2020)
Agricultural prices variation analysis is essential for the formulation of public policies and business decisions. Considering the strategic importance of olive oil for producers and consumers alike, as well as its potential economic and social benefits, this study aims to quantify the volatility of olive oil prices. The models are estimated using monthly data of olive oil prices (from January 1980 to February 2017) that was collected from IMF statistics. ARCH and GARCH models were used to estimate price volatility. Our results for olive oil show that volatility clashes of prices does not last for a long period of time, and thus olive oil is an interesting culture for new producer markets, as it is not a product that suffers from a huge volatility in price in the international market, mitigating the risk to rural producers and encouraging new local businesses. This study is limited by the data analysed and the methodology used. Further research should include more data and other statistical approaches (e.g., econometric panel data that considers different countries and several explanatory variables for price volatility). Keywords: Olive oil, volatility, ARCH, and GARCH. JEL Classifications: Q02; Q42; O13 DOI: https://doi.org/10.32479/ijeep.9138